(untitled) (Педагогіка вищої та середньої школи, 2022)
The article reveals the role of a folk fairy-tale in the process of forming younger school-children’s morality. The folklore genre is characterized as an effective means for humanistic upbringing of children. The author gives the criteria to follow when choosing folk fairy-tales to form moral-and-ethical feelings of primary classes pupils.